Understanding Gender Expertise in the Post-Truth Era: Media Representations of Gender-Based Analysis Plus in Canada - Stephanie Paterson; Francesca Scala (International Review of Public Policy)
In this paper, we explore the post-truth era as a contextual factor in how gender expertise is constituted, challenged, and defended in policy discourse in Canadian context. Using post-structural policy analysis to explore the contours of media scrutiny and the resulting debate about gender-based analysis plus (GBA+), Canada’s approach to gender mainstreaming, we reveal that it was ultimately a debate about the role of gender/intersectional expertise within government. We demonstrate that GBA+, and the gender expertise informing it, was often represented in mainstream media as either a “political intervention” or as a “technical tool”, both of which reinforce traditional representations of policy expertise, including political neutrality and professional competence, which, in the past, have been used to justify the exclusion of “other” forms of knowledge. In unpacking these representations, we suggest that, even among critics of post-truth claims, post-truth discourse offers a new vocabulary, anchored in what Ringrose (2018, 653) refers to as “post-truth anti-feminism”, which emphasizes not simply identity politics, but also potential harm resulting from interventions based on feminist knowledge. We also suggest that such claims have resulted in a distancing between gender expertise and feminism, thus contributing to the erasure of feminist knowledge in policy contexts.